1570 From <10 miu/ml to >100 miu/ml post administration of combined hepatitis a&b vaccination to non-responder healthcare workers in the hse south east. (24th April 2018) - Howard, AM
Abstract : Introduction: In 2008, the Journal of Infectious Diseases published a paper called' Excellent response rate to a double dose of a combined Hepatitis A and B vaccine in previous non responders to Hepatitis B vaccine. In 2013 the National Immunisation guidelines of Ireland introduced into their Hepatitis B schedule 'administration of a double dose of combined Hepatitis A and B vaccine can induce a protective antibody response in some previous non responders' In Occupational Health HSE South East we took this research and guidelines on board and developed a protocol on Combined Hepatitis A and B vaccination. Method: We initially looked at all our Exposure Prone Procedure (EPP) category 1 workers who were non responders to Hepatitis B and offered them the vaccine. Most of these workers had primary and secondary Hepatitis B courses. Since then we have now extended this to our category 2 workers those that are non responders to Hepatitis B but are not EPP workers. Along with development of the protocol we added an episode to our Occupational Health computer package and set up a Combined Hepatitis A and B episode with recall schedule at 0, 1 and 6 months followed by serology check 2 months post vaccination. Results: To date we have 105 healthcare workers on the Combined Hepatitis A and B course. 67 Females 38 Males Age Profile – 29% within the 41–50 age group, 28% within the 31–40 age group and 22% within the 51–60 age group. 60 Healthcare workers have completed the course and of the 60, 55 have seroconverted between >10 mIU/ml to over 100 mIU/ml a success rate so far of 91.6%. Discussion: There are still 25 healthcare workers in the middle of the Combined Hepatitis A and B course, when they are all complete we will have a greater picture. It may be worth opening a discussion on whether Combined Hepatitis A and B vaccine should be considered as a secondary course if the healthcare worker is a non responder after a primary course.